52 Immediate Management Following Cardiac Implantable Electronic Device Procedures; Wide Variation in Practice from a UK Survey. (3rd June 2016) - Bowers, Robert; Parish, Alison; Balasubramaniam, Richard; Paisey, John; Sopher, Mark
Abstract : Introduction: Following the implantation of a CIED a number of checks are made to document device function and exclude procedure complications. Traditionally these have been performed the day after the procedure, mandating an overnight admission. Recently, both the need for these investigations and their timings have been questioned, especially in the context of same day discharge practices. Methods: Staff at the largest volume device implant centres in the UK as well as to a selection of other implant centres chosen on an ad hoc basis were surveyed. Responses were received from 31 centres. The aim of the study was to assess the range of post implant practice currently used in the UK relating to device procedures where a new lead was introduced. Results: A range of practices were described relating to the timing and use of both CXR and device checks. 35.5% of centres did not mandate a post procedure CXR. At these centres, the most common reasons for requiring a CXR were the type of access used and the suspicion of procedure complication. Use of device checks once a patient had left theatre also varied. Most centres performed a full interrogation, however 4 used only a 12 lead ECG, one a magnet check and one required no further check other than that performed on the table at the end of the case. Timings for the CXR and check were similar within a centre but differed significantly between centres. 65% of centres responded to indicate that both investigations could be performed after a wait of 4 h or less from the time of implant. Same day discharge following bradycardia device implant was considered at 68% of centres and 55% of centres following ICD/CRT device procedures. A number of factors were said to be used to guide its suitability. Routine echo optimisation of all CRT devices was only reported by 16% of centres. Conclusion: There is a broad range of different practice between UK centres, relating to both the timing and use of CXR and device checks. Although still carried out in a large number of centres, traditional next day checks are no longer the norm.